Ecological Factors Determining Abundance of Parasitic Mites on Aedes spp. Larvae - Nurhadi Eko Firmansyah; Susi Soviana; Bambang Heru Budianto (Biosaintifika: Journal of Biology & Biology Education, 2017)
Ability to infestation and abundance of parasitic mites in Aedes spp. larvae cannot be separated from the influence of various factors. Ecological factors have been suggested to play a role determine the presence of parasitic mites that under certain conditions become a key factor in determining the abundance of parasitic mites on Aedes spp. larvae. The aim of this study to determine the ecological factors affect the abundance of parasitic mites on Aedes spp. larvae in Bogor Regency. Capturing of Aedes spp. larvae was performed directly on the habitats found in indoor and outdoor. Capturing mites in the body of Aedes spp. larvae was performed using insect forceps. Ecological factors measured were dissolved oxygen (DO), pH, temperature, and total dissolved solid (TDS). The influence of ecological factors was analyzed using regression and correlation analysis. The result of mite identification has been obtained three species of mites that are Halacarus sp., Histiostoma sp., and Hydrozetes sp. The result indicated that total dissolved solid (TDS) and temperature was the factors that determined the abundance of mites. The factors of pH, and dissolved oxygen (DO) did not determine the abundance of parasitic mites of Aedes spp. larvae. The research result can be further developed as a new alternative to Dengue Hemorraghic Fever control and provide information on parasitic mites that infest Aedes spp. larvae. In addition, this results become an early step in controlling of Aedes spp. strategy platform by the parasitic mites.